Factors associated with COVID-19 vaccine hesitancy: a community-based household survey in Pune district of Maharashtra, India - Saddichha D. Marathe; Shalini Bassi; Nishibha Thapliyal; Bhrunal Prakshale; Vinod G. Shah; Subhash Salunke (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background In the wake of the coronavirus (COVID-19) pandemic, the development of the COVID-19 vaccine became a game-changing tool. However, the rapid development of the COVID-19 vaccine gave rise to various myths, misconceptions and hesitancies among people. # Methods A community-based household survey was conducted by the trained healthcare workers, i.e., Accredited Social Health Activist (ASHA) and Anganwadi Worker (AWW) in their respective villages. Information on socio-demographic profile, vaccination status and reasons for vaccine hesitancy in community members was collected during the survey. Details of the vaccination status of community members were cross-examined with government vaccination data. After survey administration, continuous sensitisation to every individual was carried out by trained healthcare workers making people aware and motivating them to vaccinate. Healthcare workers constantly followed up on individuals showcasing hesitancy, thereby building up vaccine confidence in them. # Results Out of the total study population (N=12,812), 90.1% were found eligible for COVID-19 vaccination (\>18 years), 57.8% individuals had received both doses of COVID-19 vaccine, and 23.2% had received only the first dose (partially vaccinated), whereas 9.1% were unvaccinated. The most reported vaccine hesitancy response was being worried about vaccine side effects at 9.2%. The other set of reasons reported among aged 60 years and above were being old (1.6%) and having a co-morbid condition (1.1%). Having an underlying illness was also reported in both age groups (45-60 years, and 60 years and older). Additionally, 18.2% of the unvaccinated and partially vaccinated eligible individuals reported planning to get vaccinated soon. # Conclusions The study reported many myths and misconceptions, and hesitancies related to the COVID-19 vaccine among the community members being a major lag in the vaccine acceptance and uptake. Therefore, adequate vaccine education is much needed to engage the non-medical group, as they mostly tend to have positive interactions with the community members. On that account, sustained community-based health promotion intervention can be effective.